An Evaluation of the Quality of Care in Fertility and Infertility Services in Tripoli Health Centers - Fatma Elmontaser (AlQalam Journal of Medical and Applied Sciences, 2025)
Fertility and infertility services play an important role in healthcare, especially as more people delay having children, face unhealthy lifestyles, and deal with environmental pollution. This study aims to improve the quality of these services. The study focuses on making medical care safer and more effective, reducing errors, and improving the patient experience. It also seeks to boost success rates in fertility treatments, ensure fair access to reproductive healthcare, and offer physical and emotional support to patients. A cross-sectional study was carried out from October 2024 to April 2025. A questionnaire was given to 116 people using fertility and infertility services. The study examined service quality, accessibility, medical care, financial and emotional challenges, and overall satisfaction. The study found major barriers to accessing fertility services, with cost (57.76%) and waiting times (17.24%) being the biggest issues. Service quality was mostly rated as "good" (31.90%). Participants suggested making services more affordable (57.76%) and improving online access to information (44.83%). Addressing these barriers can lead to safer, more effective care, better treatment outcomes, and stronger emotional and physical support for patients. By prioritizing affordability, efficiency, and patient-centered care, fertility services can become more inclusive and effective for those in need.